Regulated microarchitecture, spin polarization state, and observed charge transfers for cerium boride CeB6 under electrical Field. (March 2021) - Zhang, F.P.; Sun, Y.; Wang, H.H.; Zhang, G.L.; Qin, G.Q.; Zhang, J.X.
Graphical abstract: Highlights: The physical properties of CeB6 under electrical field have been investigated. The CeB6 under electrical field is more stable. The B polyhedron in CeB6 is regulated. The physical properties of CeB6 can be regulated. Abstract: The thermal stabilities, microarchitectures as well as the electronic states of the cubic CeB6 under electrical field have been systematically investigated in detail within the framework of plane wave pseudo-potential density functional theory calculational method. Specifically, theCeB6 under electrical field of 0.0002 V/Å has lower total energy and enthalpy of formation. The cell of theCeB6 under electrical field is slightly expanded and the lattice expansion is isotropic, along with microarchitecture regulations. The distances between B are 2.523 Å, 1.707 Å and 1.784 Å, showing covalent bonds. There are 5 sub-bands for CeB6, the energy widths of bands are regulated with the conduction band and the first valence band moving downwards under electrical field. There are 3 band valleys and 5 band peaks for the CeB6, with metallic transition and decreased band gaps under electrical field. The middle conduction band and the first valence band are formed by f, d and p orbital electrons, respectively. The Ce s and the B orbital electrons tend to polarize under electrical field. The Ce f, Ce s and B orbital electrons are responsible for the ferrimagnetic magnetism under electrical field. There are charge transfers among these orbitals for CeB6 under electrical field.